2013
DOI: 10.1016/j.jbtep.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Are attentional bias and memory bias for negative words causally related?

Abstract: Background and Objectives: In cognitive theories of depression, processing biases are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…Moreover, there is some evidence for transfer of ABM to memory. A study reported that participants with elevated depressive symptom severity levels trained to orient away from negative words did not show a negative recollection bias which was observed in control individuals (Blaut, Paulewicz, Szastok, Prochwicz, & Koster, 2013). In sum, research indicates that dot-probe training effects transfer to new, non-trained stimuli under similar conditions, but provides mixed evidence regarding transfer to other critical processes.…”
Section: Transfer Of Single-session Abmmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, there is some evidence for transfer of ABM to memory. A study reported that participants with elevated depressive symptom severity levels trained to orient away from negative words did not show a negative recollection bias which was observed in control individuals (Blaut, Paulewicz, Szastok, Prochwicz, & Koster, 2013). In sum, research indicates that dot-probe training effects transfer to new, non-trained stimuli under similar conditions, but provides mixed evidence regarding transfer to other critical processes.…”
Section: Transfer Of Single-session Abmmentioning
confidence: 93%
“…Of final note, the limited range of psychopathology may have obscured training and transfer effects. Studies by Blaut et al (2013) and Arditte and Joormann (2014) observed training or transfer at higher levels of depression or rumination. The restricted range of affective symptoms in the current experiments limits exploration of such moderation effects.…”
Section: Transfer Of Single-session Abm 21mentioning
confidence: 98%
“…The negative memory bias in depression can be accounted for by attentional biases (33). Mood-congruent attentional biases have been found in individuals with depression and dysphoria (114,142,159,226).…”
Section: Reproductive Steroids: Regulators Of Affective State Affectimentioning
confidence: 97%
“…There were three main hypotheses: First, we hypothesized that participants who viewed the thin-body images for a longer duration (and paid more attention) in the present study would have better recognition memory of those images than would participants who viewed them for a shorter duration [7,8,15]. Second, based on cognitive theories [4,5,14], we expected that participants' recognition memory for the thin-body images would lead to increased body dissatisfaction (i.e., a larger actual-ideal discrepancy).…”
Section: Introductionmentioning
confidence: 99%
“…Research based on cognitive theories of eating disorders [4,5] has emphasized the important roles that increased attention to and better memory for body-related information play in the development and maintenance of such body image issues [6], but the exact nature of the relationship between these biases and their impact on women's body image concerns is not well understood. There is evidence in the depression literature that biases in attention and memory are related [7,8], but these associations have not been tested in the body image literature. Thus, the purpose of the present study was to test the relationships between attention and memory biases and women's body dissatisfaction that have been proposed by cognitive models but that remain untested.…”
Section: Introductionmentioning
confidence: 99%